UNMASKING DECEPTION IN THE AGE OF ARTIFICIAL INTELLIGENCE: A COMPREHENSIVE ANALYSIS OF INDIAN CELEBRITY’S DEEPFAKES NEWS - Panda, Jayanta Kumar; Panigrahy, Rajnandini (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The rapid advancement of Artificial Intelligence (AI), Machine Learning (ML), and Deep Learning (DL) has ushered in a new era of digital disruption, particularly in the domain of disinformation and content manipulation. Among the various applications emerging from this progress, the phenomenon of deepfakes has emerged as a formidable challenge. Deepfakes represent synthetic media productions, intricately crafted through AI algorithms, with the ability to seamlessly replace a person's likeness in videos or images. The consequences of deepfakes are profound, encompassing the propagation of misinformation, reputation damage, and erosion of trust in digital content. The rising cases of deepfake news underscore a significant threat in the field of artificial intelligence. To mitigate this issue a comprehensive strategy requires to development of awareness, education, technological advancements, and strong legal frameworks to safeguard identities and curtail the misuse of deepfakes. This involves key steps like the development of detection technologies, the establishment of clear legal guidelines, heightened public awareness, empowerment of individuals, and promotion of responsible AI use. This paper conducts an in-depth analysis of three case studies involving prominent Indian celebrities—Rashmika Mandhana, Kajol Devgan, and Katrina Kaif—affected by deepfake news. The prime objective of the research is to understand the key factors that determine the authenticity of these deepfake contents to combat the spread of misinformation by promoting responsible AI usage and fostering a culture of digital literacy. Through concerted efforts encompassing technological innovation, legal reform, public awareness, and individual empowerment, the researcher tries to counter the threat posed by Deepfakes and uphold the integrity of digital discourse in the age of AI.